Karyotype asymmetry shapes diversity within the physaloids (Physalidinae, Physalideae, Solanaceae). Issue 2 (28th November 2020) - Rodríguez, Julieta; Deanna, Rocío; Chiarini, Franco
Abstract : Within the cosmopolitan family Solanaceae, Physalideae is the tribe with the highest generic diversity (30 genera and more than 200 species). This tribe embraces subtribe Physalidinae, in which phylogenetic relationships of some genera are not entirely resolved. Chromosomes may help on resolution, by providing information on the processes underlying speciation. Thus, cytogenetic analyses were carried out in the subtribe in order to establish its chromosome number and morphology. Physalidinae is characterized by x = 12 and most species shows a karyotype more asymmetric than those of sister clade Iochrominae. These karyotype traits were mapped onto a molecular phylogeny to test the congruence between karyotype evolution and clade differentiation. A diploid ancestor was reconstructed for the subtribe, and five to six polyploidy independent events were estimated, plus one aneuploidy event (X = 11 in the monotypic genus Quincula ). Comparative phylogenetic methods showed that asymmetry indices and mean arm ratio (r) have a high phylogenetic signal, whereas a single gain of subtelocentric/telocentric chromosomes was found in the common ancestor of Physalis, Quincula, and Chamaesaracha . Karyotype asymmetry allows us to differentiate genera within subtribe Physalidinae. Overall, our study suggests that diversification in this group has been accompanied by karyotype changes, which can also be applied to delimit genera.